2021
DOI: 10.14302/issn.2641-4538.jphi-20-3683
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Factors Associated with Overweight and Obesity Prevention among Women Attending Kibagabaga Hospital, Rwanda

Abstract: Women in Rwanda are still suffering from overweight and obesity and health-related complications. However, little is known about overweight/obesity prevention knowledge and factors associated with overweight/obesity prevention among women. The aim of this study was to determine knowledge and factors associated with overweight and obesity prevention among women attending Kibagabaga Hospital in Rwanda. A quantitative descriptive cross-sectional design was conducted among women aged 20-45 years that was selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(6 reference statements)
0
3
1
Order By: Relevance
“…This implies that participants had no enough knowledge on weight management to prevent overweight/obesity. Contrary to the current findings, a study done in Rwanda revealed that 22% of participants had higher knowledge and 62% had moderate knowledge on prevention of overweight and obesity [24]. The same study also reported that more than half of the participants have knowledge on different components for preventing overweight and obesity including the causes, whereby eating too much fat foods and insufficient physical activity were both mentioned as the causes of overweight and obesity which is again contrary to the current study whereby very few individuals have knowledge on prevention of overweight/obesity.…”
Section: Plos Onecontrasting
confidence: 99%
See 1 more Smart Citation
“…This implies that participants had no enough knowledge on weight management to prevent overweight/obesity. Contrary to the current findings, a study done in Rwanda revealed that 22% of participants had higher knowledge and 62% had moderate knowledge on prevention of overweight and obesity [24]. The same study also reported that more than half of the participants have knowledge on different components for preventing overweight and obesity including the causes, whereby eating too much fat foods and insufficient physical activity were both mentioned as the causes of overweight and obesity which is again contrary to the current study whereby very few individuals have knowledge on prevention of overweight/obesity.…”
Section: Plos Onecontrasting
confidence: 99%
“…The reported high prevalence of overweight/obesity was positively associated with female sex which may be due to cultural aspects and preference of women appearance because among the participants who reported to be concerned with their body weight to ensure good appearance, majority was females. A similar study in Rwanda by Niyitegeka et al [ 24 ] reported that in most areas of Africa, overweight/obesity is regarded as a sign of good nutrition, happiness and improved socio-economic conditions. The high prevalence of overweight/obesity was also reported in rural and semi-urban areas of Kilimanjaro to be a result of providing women with a leave of at least three months from household chores and other activities which may reduce their energy expenditure leading to increased prevalence of overweight and obesity [ 25 ].…”
Section: Discussionmentioning
confidence: 89%
“…In another study in Rwanda that included mostly urban participants, it was observed that unemployed workers and people employed in public sector were more likely to avoid obesity (less likely to be obese) than the workers employed in the informal (private) sector [ 39 ]. This is in direct contrast to the findings of the present study, and those of the Kenyan study.…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic factors like age [19,[26][27][28], level of education [19] marital status [26], number of children [28], wealth [19,[26][27][28][29], household size [28] being female [27,29] and urban residence [19,[27][28][29] are known to be associated with obesity in Uganda. Studies elsewhere in Africa have reported a positive association between urban residence and obesity among women [30], as well as employment/ working status [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%